Customer satisfaction on Malay food restaurant at Pahang / Wan Nor Syuhana Wan Mahamad Hanafi - Wan Mahamad Hanafi, Wan Nor Syuhana (2017)
Restaurant not only seen as one of important entity in Malaysian service sector but it also as part of national economic booster in recent year. This undergraduate project aim to determine the factors that contribute to customer satisfaction in Malay food restaurants and determine the most influential factor among three factors that contribute to customer satisfaction. In this paper, researcher will implemented a argumentative research design as a guide in the process of collecting data. The finding of the study show that price, service quality, and environment has positive effect in customer satisfaction. Price are the most influential factor that contribute to customer satisfaction.